Incontinence and gait disturbance after intraventricular extension of intracerebral hemorrhage. (8th March 2016) - Woo, Daniel; Kruger, Andrew J.; Sekar, Padmini; Haverbusch, Mary; Osborne, Jennifer; Moomaw, Charles J.; Martini, Sharyl; Hosseini, Shahla M.; Ferioli, Simona; Worrall, Bradford B.; Elkind, Mitchell S.V.; Sung, Gene; et al.
Abstract : Objective: We tested the hypothesis that intraventricular hemorrhage (IVH) is associated with incontinence and gait disturbance among survivors of intracerebral hemorrhage (ICH) at 3-month follow-ups. Methods: The Genetic and Environmental Risk Factors for Hemorrhagic Stroke study was used as the discovery set. The Ethnic/Racial Variations of Intracerebral Hemorrhage study served as a replication set. Both studies performed prospective hot-pursuit recruitment of ICH cases with 3-month follow-up. Multivariable logistic regression analyses were computed to identify risk factors for incontinence and gait dysmobility at 3 months after ICH. Results: The study population consisted of 307 ICH cases in the discovery set and 1, 374 cases in the replication set. In the discovery set, we found that increasing IVH volume was associated with incontinence (odds ratio [OR] 1.50; 95% confidence interval [CI] 1.10–2.06) and dysmobility (OR 1.58; 95% CI 1.17–2.15) after controlling for ICH location, initial ICH volume, age, baseline modified Rankin Scale score, sex, and admission Glasgow Coma Scale score. In the replication set, increasing IVH volume was also associated with both incontinence (OR 1.42; 95% CI 1.27–1.60) and dysmobility (OR 1.40; 95% CI 1.24–1.57) after controlling for the same variables. Conclusion: ICH subjects with IVH extension are at an increased risk for developing incontinence and dysmobility after controlling for factors associated with severity and disability. This finding suggests a potential target to prevent or treat long-term disability after ICH with IVH.